2010
DOI: 10.1371/journal.pone.0010947
|View full text |Cite
|
Sign up to set email alerts
|

Random X Inactivation and Extensive Mosaicism in Human Placenta Revealed by Analysis of Allele-Specific Gene Expression along the X Chromosome

Abstract: Imprinted inactivation of the paternal X chromosome in marsupials is the primordial mechanism of dosage compensation for X-linked genes between females and males in Therians. In Eutherian mammals, X chromosome inactivation (XCI) evolved into a random process in cells from the embryo proper, where either the maternal or paternal X can be inactivated. However, species like mouse and bovine maintained imprinted XCI exclusively in extraembryonic tissues. The existence of imprinted XCI in humans remains controversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 43 publications
4
82
0
11
Order By: Relevance
“…In human embryos, XIST expression is detected from the 4-8-cell stage and XCI has been proposed to follow kinetics similar to those in mouse 21 , although it does not seem to be imprinted in extra-embryonic tissues 22,23 . To investigate this further, we examined in vitro conceived pre-implantation human embryos ( Fig.…”
mentioning
confidence: 99%
“…In human embryos, XIST expression is detected from the 4-8-cell stage and XCI has been proposed to follow kinetics similar to those in mouse 21 , although it does not seem to be imprinted in extra-embryonic tissues 22,23 . To investigate this further, we examined in vitro conceived pre-implantation human embryos ( Fig.…”
mentioning
confidence: 99%
“…It was also reported that this site was unmethylated in microdissected stromal tissue from placenta and umbilical cord (Looijenga et al 1999). Second, the villous trees of the placenta grow in a highly clonal manner (see below), creating extensive site-tosite differences in XCI status (Moriera de Mello et al 2010;Peñaherrera et al 2012). Last, the average level of skewing over multiple sampled sites shows little correlation with skewing observed in fetal somatic tissues (Peñaherrera et al 2012).…”
Section: Hypomethylation Of X-chromosome Gene Promoters In Femalesmentioning
confidence: 99%
“…Some studies demonstrated that X-inactivation was also imprinted in the human placenta (Harrison & Warburton 1986), whereas other studies reported that it was random (Moreira de Mello et al 2010). It should be mentioned, however, that in contrast to mice, an extra X chromosome(s) can be maternal or paternal in origin in Klinefelter syndrome patients (47, XXY).…”
Section: Imprinted X Chromosome Inactivationmentioning
confidence: 99%